Documentation of Underutilized Fruit Trees (UFTs) across indigenous communities in West Java, Indonesia - Mochammad Fikry Pratama; ANGGA DWIARTAMA; DIAN ROSLEINE; RIZQI ABDULHARIS; ARIFIN SURYA DWIPA IRSYAM (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Pratama MF, Dwiartama A, Rosleine D, Abdulharis R, Irsyam ASD. 2019. Documentation of Underutilized Fruit Trees (UFTs) across indigenous communities in West Java, Indonesia. Biodiversitas 20: 2603-2611. Fruit as a source of food has been mostly underrated, while in fact play a role in providing nutritional security as well as contributing to the integrity of local ecosystems. The declining significance of local indigenous fruits, often referred to as underutilized fruits, in rural populations may have an unprecedented consequence to the availability of high-quality resources for the wider society. This article, therefore, sees this importance by documenting the existence of underutilized fruit-trees across indigenous communities, often acknowledged to be the chaperones of local biodiversity. Using a combined method of interviews, exploratory observation and vegetation analysis in seven indigenous communities in West Java Province, this study investigated the role and position of fruit-tree species in their ecological landscapes and communities' knowledge systems. The article documents 75 fruit tree species, 38 out of which are categorized as underutilized. The proportion of this group of species to the total fruit tree species varied between 0 to 45%. Further analysis found that the underutilized fruit trees were far smaller in abundance compared to commercial timber, fruit, and other trees. We conclude that efforts to uplift the conservation value of these fruit-trees can begin via promotion and market development by multiple stakeholders.